2013
DOI: 10.1007/s00127-013-0765-0
|View full text |Cite
|
Sign up to set email alerts
|

Cancer mortality among psychiatric patients treated in a community-based system of care: a 25-year case register study

Abstract: Psychiatric patients showed different patterns of site-specific cancer mortality when compared with the general population. The 20-fold higher risk of dying from hematological neoplasms needs further investigation. Chronic use of phenothiazines could be involved in the relative protection from stomach and prostate cancer found in psychiatric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 31 publications
0
28
0
Order By: Relevance
“…This register has contributed continuously to the international literature over a span of more than 30 years, documenting the importance of smaller, intensive clinical registers. Examples of this are studies about a highly relevant topic: mortality among psychiatric patients , avoidable mortality , and health economic aspects of community psychiatry .…”
Section: Discussionmentioning
confidence: 99%
“…This register has contributed continuously to the international literature over a span of more than 30 years, documenting the importance of smaller, intensive clinical registers. Examples of this are studies about a highly relevant topic: mortality among psychiatric patients , avoidable mortality , and health economic aspects of community psychiatry .…”
Section: Discussionmentioning
confidence: 99%
“…From these results, it seems important the implementation, by specialist psychiatric services, of health promotion and preventive programmes specifically targeted to psychiatric patients . Long lasting follow‐ups, that is, 25‐years in our case , allowed also to study different patterns of site‐specific cancer mortality among psychiatric patients, showing an increased SMRs for cancer of the oral cavity (22.93), lymphoma, leukaemias, Hodgkin's lymphoma (8.01) and central nervous system (CNS) and cranial nerve tumours (4.75). The SMR decreased for stomach tumours (0.49).…”
mentioning
confidence: 73%
“…follow-up may not have been suffi cient for any conclusions to reach a level of signifi cance. There are no survival studies specifi c to Axis II patients, however one that evaluated cancer deaths among a psychiatric population (Perini et al 2013) found personality disorders as being one of the independent risk factors to higher mortality in specifi c anatomic sites (standardized mortality ratios ϭ 28 for the central nervous system) together with alcoholism (5.9 for the larynx) and affective disorders (20 for lymphomas).…”
Section: Discussionmentioning
confidence: 99%